Internet‐based interventions for postpartum depression: A systematic review and meta‐analysis. Issue 3 (29th December 2020) - Mu, Ting‐Yu; Li, Yu‐Hong; Xu, Ri‐Xiang; Chen, Jun; Wang, Ya‐Ya; Shen, Cui‐Zhen
Abstract: Aim: To determine the efficacy of Internet‐based interventions in decreasing the prevalence of postpartum depression in perinatal women. Design: This review was conducted according to the standards outlined in the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses statement. Methods: We performed a systematic meta‐analysis of randomized controlled trials on the efficacy of Internet‐based interventions for postpartum depression. Studies (2008–2018) were identified through a search conducted on PubMed, EMBASE and the Cochrane Library. Risk ratios or weighted mean differences with 95% confidence intervals were calculated using a fixed‐effects model or a random‐effects model. Stata software 11.0 was used to perform the meta‐analysis. Results: Most of the seven eligible studies were randomized controlled trials. The random‐effects model indicated that Internet‐based interventions significantly improved postpartum depression ( d  = 0.642, N  = 7). Attrition rates ranged from 4.5%–86.9% and from 0%–87.1% for the intervention and control groups, respectively.